RANCANG BANGUN WEB SERVICE BERBASIS JSON PADA WEBSITE PARIWISATA SEMARANG STUDI KASUS PADA TOKO SOUVENIR GAMBANG SEMARANG (Information Technology and Telematics, 2013)
Abstract-- This study examines the exchange of  data between  Gambang  Semarang  Souvenir  Shop  Website with Semarang Tourism Website using web  service applications with  JSON protocol. The  problem is  how to  make a web service  applications   that  can  share  information  between Gambang  Semarang  Souvenir  Shop  Website  with  Tourism Website  Semarang,  so  that  users  in  Semarang   Tourism Website can also see information held  Gambang Semarang Souvenir Shop Website. The  study  produced  a  web  application  service  with JSON protocol that has a function - a function  that can be used  to share data between  Gambang  Semarang  Souvenir Shop Website with Semarang Tourism Website. Through this system is expected to hopefully  Gambang Semarang   Souvenir   Shop   can   get   more   customers   by displaying  its  tourism  packet  data  in  Semarang  Tourism Website. For future improvement, complement and extend the functionality of the web service to plan the next steps. Keywords: Web Service, JSON